2015
DOI: 10.1002/cctc.201500200
|View full text |Cite
|
Sign up to set email alerts
|

Pd‐Catalyzed Z‐Selective Semihydrogenation of Alkynes: Determining the Type of Active Species

Abstract: A protocol was developed to distinguish between well‐defined molecular and nanoparticle‐based catalysts for the Pd‐catalyzed semihydrogenation reaction of alkynes to Z‐alkenes. The protocol applies quantitative partial poisoning and dynamic light scattering methods, which allow the institution of additional validation experiments. For the quantitative partial poisoning method, tetramethylthiourea (TMTU) was developed as an alternative for the standard poison ligand CS2, and was found to be superior in its appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 111 publications
1
17
0
1
Order By: Relevance
“…For instance, Medlin and co-workers have demonstrated that the catalytic properties of Pd and Pt catalysts can be well controlled by coating n-alkane thiols on their surfaces. [33][34][35][36] Although the importance of thiols or other sulfur-containing species in promoting palladium catalysis has been well understood in some Pd-complex systems, [37][38][39] determination of the detailed surface and interface structure of thiolated-protected Pd nanocatalysts, and thus understanding the molecular mechanism behind the catalytic enhancements, remains challenging.…”
Section: The Bigger Picturementioning
confidence: 99%
“…For instance, Medlin and co-workers have demonstrated that the catalytic properties of Pd and Pt catalysts can be well controlled by coating n-alkane thiols on their surfaces. [33][34][35][36] Although the importance of thiols or other sulfur-containing species in promoting palladium catalysis has been well understood in some Pd-complex systems, [37][38][39] determination of the detailed surface and interface structure of thiolated-protected Pd nanocatalysts, and thus understanding the molecular mechanism behind the catalytic enhancements, remains challenging.…”
Section: The Bigger Picturementioning
confidence: 99%
“…It should be noted that a distinction between catalytic activity of Pd NPs and a molecular catalyst in phenylacetylene semihydrogenation is often problematic. [41] Interaction of the [Pd-(pymo) 2 ] n with BH 4 À resulted in formation of hydrido species, active in molecular hydrogenation. However, during formation of styrene, the MOF structure collapses forming Pd NPs which next catalyze the reaction.…”
Section: Catalyst Transformationsmentioning
confidence: 99%
“…The To further investigate the reaction mechanism, we performed partial poisoning studies using TEMPO (2,2,6,6-tetramethylpiperidine-1-oxyl) as a radical inhibitor and TMTU (tetramethylthiourea) as a strongly binding poison (28). With both reagents, the reaction was completely inhibited by one equivalent per catalyst, and for TMTU, only half an equivalent was sufficient ( fig.…”
mentioning
confidence: 99%